Gaya pembelajaran pelajar diploma dalam mempelajari bahasa Jerman / Rowinah Jakiwa - Jakiwa, Rowinah (2012)
The purpose of this research is to identify the learning style of Diploma students in learning German language at German-Malaysian Institute and to find out the relationship between the learning styles and the academic achievement. A total of 190 Diploma students from different year of studies and courses at GMI involved in this study. The respondents comprised of 108 male and 82 female students. Data which is collected by using Index of Learning Style (1991) questionnaire and analyzed by using Statistical Package for Social Sciences (SPSS) 16.0. The findings of this research show that the student’s main learning style is Visual (84.7%), followed by balance Sensing & Intuitive (70.5%) and balance Sequential & Global (66.8%). Both male and female students are more on Visual learning style. In conclusion, there is no significant difference among gender and courses. The finding also shows that there is no significant relationship between learning styles and academic achievement.